Living with Dwarfism: Experience of Individuals Living with with Dwarfism in Palak Siring Village from Interpersonal Communication Perspective - Hidayat, Arif; Meilia, Giovani Eka; Saputra, Muhammad Agusti; Wicaksono, Banyu (Faculty of Psychology, Universitas Negeri Yogyakarta, 2021)
Having a perfect physique is the aspiration of every human being. However, some people have to live with rare occurrence of dwarfism caused by several factors. Palak Siring Village located in Bengkulu, is a village with one of the highest population of people with dwarfism in Indonesia. This current study aims to explore the forms of interpersonal communication, and the factors causing the existence of dwarf humans in Palak Siring Village. This research is qualitative descriptive research with analytical method. The participants of this study are people with dwarfism living in Palak Siring Village. Data was collected using closed-ended questionnaires, interpersonal communication questionnaires, and interview. The results showed that the existence of people with dwarfism in Palak Siring Villade is due to the hereditary factor of genes inherited from mother's side. The genes was said to be originated from women in Padang Guci Kaur that moved to Kedurang and Palak Siring Village. Living experience includes able to communicate well, being noticed by many people, having access to higher education, being able to operate social media, and having been covered in various media. Whereas the form of interpersonal communication is carried out through three stages, namely the approach process, building communication and developing credibility. In supporting effective communication, there are several aspects that are used such as aspects of openness, empathy, supportive attitude, positive attitude, and equality.